Penguatan Kesiapsiagaan Bencana Alam melalui Edukasi Kebencanaan - Reni Alfiyah; A Hardiyanti; Riri Amandaria; Hudayah Sulaiman; Ramdani Sidik (Abdimas Mandalika, 2026)
Abstract:  The vulnerability of students to disaster risks requires a systematic and contextual educational intervention within the school environment. This community service activity aims to optimize student preparedness through the strengthening of disaster literacy at SMP Negeri 1 Balocci. The approach used involves interactive socialization emphasizing active student participation through reflective dialogue, presentation of locally-based material, and simple simulations related to mitigation and evacuation steps. This strategy is not only oriented toward knowledge transfer but also toward the formation of critical awareness and adaptive responses to potential disasters. The implementation results show an increase in students' cognitive and affective capacities in recognizing types of disasters, understanding the mechanisms of their occurrence, and determining appropriate actions before, during, and after disasters. High student involvement during the activities serves as an indicator of the effectiveness of the approach used. Therefore, this program has implications for the importance of integrating disaster education into continuous learning practices as an effort to build a disaster-resilient culture in educational units.Abstrak: Kerentanan peserta didik terhadap risiko bencana menuntut adanya intervensi edukatif yang sistematis dan kontekstual di lingkungan sekolah. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengoptimalkan kesiapsiagaan siswa melalui penguatan literasi kebencanaan di SMP Negeri 1 Balocci. Pendekatan yang digunakan berupa sosialisasi interaktif dengan menekankan pada partisipasi aktif siswa melalui dialog reflektif, pemaparan materi berbasis konteks lokal, serta simulasi sederhana terkait langkah mitigasi dan evakuasi. Strategi ini tidak hanya berorientasi pada transfer pengetahuan, tetapi juga pada pembentukan kesadaran kritis dan respons adaptif terhadap potensi bencana. Hasil pelaksanaan menunjukkan terjadinya peningkatan kapasitas kognitif dan afektif siswa dalam mengenali jenis bencana, memahami mekanisme terjadinya, serta menentukan tindakan yang tepat sebelum, saat, dan setelah bencana. Keterlibatan siswa yang tinggi selama kegiatan menjadi indikator efektivitas pendekatan yang digunakan. Oleh karena itu, program ini berimplikasi pada pentingnya integrasi edukasi kebencanaan dalam praktik pembelajaran berkelanjutan sebagai upaya membangun budaya tangguh bencana di satuan pendidikan.